2013
DOI: 10.1177/0954409712472329
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of the dynamic properties of ladder track to minimise the chance of rail corrugation

Abstract: The ladder track used by the Beijing subway which can be subjected to rail corrugation is considered in this paper. Dynamic models of the vehicle and the ladder track are developed to analyse the track vibration behaviour. Using these models the effect of the most significant ladder track parameters on track vibrations are analysed in the frequency and time domains. Using experimental and numerical results the vibration frequency of the rail that is responsible for rail corrugation is determined. Based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…In the design of railway tracks, the track support system is used to control the rail oscillation. The influences of the track support system on rail corrugation have been studied extensively [18][19][20][21][22]. Ilias [18] investigated the effect of sleeper vertical stiffness from 60 MN/m to 500 MN/m on the wheel-rail interaction and corrugation growth.…”
Section: Interesting Rail Corrugation Phenomenamentioning
confidence: 99%
See 1 more Smart Citation
“…In the design of railway tracks, the track support system is used to control the rail oscillation. The influences of the track support system on rail corrugation have been studied extensively [18][19][20][21][22]. Ilias [18] investigated the effect of sleeper vertical stiffness from 60 MN/m to 500 MN/m on the wheel-rail interaction and corrugation growth.…”
Section: Interesting Rail Corrugation Phenomenamentioning
confidence: 99%
“…Jin et al [21] pointed out that the discrete sleeper is one of the main reasons of rail corrugation growth. And the optimized parameter values of the ladder track to minimize the growth of rail corrugation were investigated by Yan et al [22] Because many researchers reported that a softer track support structure contributes to restraining or eliminating rail corrugation [18,19], a specific track support structure characterized by a lower stiffness value, called "Cologne egg type sleeper", is used in metro tracks for oscillation isolation [23]. However, rail corrugation is severer than before.…”
Section: Interesting Rail Corrugation Phenomenamentioning
confidence: 99%
“…Furthermore, in some cases, rail corrugation can even result in derailment accidents. Therefore, rail corrugation is harmful and should be eliminated [2]. A large number of studies have been carried out in this area, and numerous research documents exist [3].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the first natural frequency of ladder track occurs at 33-36 Hz. To solve the problem of rail corrugation, the dynamic properties of the ladder track used in the Beijing subway were optimized by Yan et al [13,14].…”
Section: Introductionmentioning
confidence: 99%